THE ROLE OF THE CONCEPT OF COLLECTIVE SECURITY IN INTERNATIONAL LAW AND LEGAL ISSUES OF ITS IMPLEMETTAION - Zakaryan, Armen (State and Law, 2020)
The concept of collective security represents international arrangments defining international peace and security threats and the collective means of struggle against these threats. The key issues hindering implementation of collective security and effective functioning of the United Nations and the Security Council - its key body responsible for international peace and security are considerably high. If we group the international legal issues that hinder the implementation of the collective security concept, they may be divided into the following main groups: the UN Security Council’s decision-making procedures, in particular, the abuse of the veto right by the UN Security Council permanent members, attempts to create new grounds for the use of force and misuse of individual/collective self-defense.